Standardized suturing can prevent slackening or bursting suture lines in midline abdominal incisions and defects - Lesch, Carolin; Uhr, Katharina; Vollmer, Matthias; Raschidi, R.; Nessel, Regine; Kallinowski, Friedrich (Hernia, 2022)
Purpose: Incisional hernias often follow open abdominal surgery. A small-stitch–small-bite suture might close the incision durably. We analyzed specific details of this closure technique and assessed their influence on the closure stability. Methods: The effects of cyclic loads, simulating coughs were investigated on a bench test. We prepared porcine bellies in the median line and bovine flanks parallel to the muscle fibers with 15 cm long incisions. Then we punched round or rhomboid defects with a diameter of 5–10 cm into the center of the incision. Monomax® 2–0 and Maxon® 1 and 2–0 were used as suture materials. We tested the durability of the closure with pressure impacts of 210 mmHg repeated 425 times. Throughout the experiments, we modified the suturing technique, the surgeon, the tissue tension, the defect size and shape and the suture diameter. Results: Standardizing the suture technique improved the durability of the closure significantly. Any other variations showed minor influences after standardization. All incisions with round defects up to 7.5 cm width withstood 425 impacts using standardized suturing. Unstandardized sutures failed in all cases. When closing an incision with a 10 cm wide defect, the tissues ruptured frequently next to the suture line. We defined criteria to standardize this suturing technique. For the first time, we developed a suture factor related to the durability of a sutured tissue closure. We integrated the suture factor into the concept of biomechanically durable repairs. Conclusions: Suturing the abdominal wall with a standardized suturing technique improves its durability significantly.